PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR YAMAHA TIPE MX KING (Studi pada Pengguna Sepeda Motor Yamaha Tipe MX King Di Sangatta) - ANDI MUKLIS (Jurnal Administrasi Bisnis Fisipol Unmul, 2021)
This study aims to determine the influence of independent variables consisting of Price (x1) and Product Quality (x2) on dependent variables of Purchasing Decisions (Y) both partially and simultaneously and to know one of the two variables that have the most effect on Purchasing Decisions. The type of research used is a type of quantitative research. The population in this study was users of Yamaha MX King motorcycles in Sangatta. The sample count used was 90 users of Yamaha MX King motorcycles in Sangatta. The sampling technique used is incidental sampling. The data analysis techniques used in this study are validity test and reliability test, classic assumption test, multiple linear analysis, the most influential variables. The results of the calculation of test F (simultaneous) show that independent variable Price (x1), Product Quality (x2) simultaneously has an influence on dependent variables Purchase Decision (y). From the results of the T test analysis (partial) shows that the Price (x1) partially has a significant effect on the Purchase Decision (y) and Product Quality (x2) partially also affects the Purchase Decision (y) of Yamaha motorcycle type MX King in Sangatta. The variable that most affects the Purchase Decision is the Product Quality variable.